Sejarah Penulisan dan Pembukuan Alquran - Juli Julaiha; Elin Suryani; Muammar Muammar; Ikhsan Akbar Handinata (Jurnal Ilmiah Wahana Pendidikan, 2023)
At the time of the Prophet, the collection of the Koran was called the pre-codification phase (qabi' 'ashr at-tadwin). At the time of the Prophet Muhammad, writings on verses of the Koran were not written down in books, but memorized by rote. At the time of the caliph Abu Bakr, all the writings or notes of the Koran that were scattered on animal skins, bones and palm fronds were removed, then collected in one manuscript. During the time of the caliph Umar bin Khattab, he sent friends who mastered the Koran to the areas of the new Islamic daulah that were successfully controlled. During the time of the caliph Uthman bin Affan, determined the reading of the Koran according to the qira'at of the Quraysh tribe. Furthermore, during the time of the caliph Ali bin Abi Talib, refinements were made by adding dignity and punctuation marks.